2020
DOI: 10.1016/j.arthro.2019.11.104
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: Predicting the Size of the Labrum: We Have the Technology, Should We Put it to Use?

Abstract: The size of the labrum of the hip found at the time of arthroscopy can be predicted by measuring the labrum on preoperative magnetic resonance imaging/magnetic resonance arthrography, which may lead to consideration of using this measurement for preoperative planning. While normal labral anatomy is becoming better understood and our ability to preoperatively evaluate this improves, more evaluation is warranted to determine if, and at what point, labral width should influence treatment decisions, including labr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Width has been identified as the most important component of the labrum with regards to conferring the suction seal effect. 9 , 10 A recent study demonstrated that decreased labral width is associated with significantly worse functional outcomes following arthroscopic labral repair and treatment of FAI. 11 While it has been established that GJH is associated with hip capsule thickness and microinstability, there is limited information on how GJH relates to labral width.…”
mentioning
confidence: 99%
“…Width has been identified as the most important component of the labrum with regards to conferring the suction seal effect. 9 , 10 A recent study demonstrated that decreased labral width is associated with significantly worse functional outcomes following arthroscopic labral repair and treatment of FAI. 11 While it has been established that GJH is associated with hip capsule thickness and microinstability, there is limited information on how GJH relates to labral width.…”
mentioning
confidence: 99%